2015
DOI: 10.1128/jvi.01989-15
|View full text |Cite
|
Sign up to set email alerts
|

Immune Protection against Virus Challenge in Aging Mice Is Not Affected by Latent Herpesviral Infections

Abstract: f Latent herpesvirus infections alter immune homeostasis. To understand if this results in aging-related loss of immune protection against emerging infections, we challenged old mice carrying latent mouse cytomegalovirus (CMV), herpes simplex virus 1 (HSV-1), and/or murine gammaherpesvirus 68 (MHV-68) with influenza virus, West Nile virus (WNV), or vesicular stomatitis virus (VSV). We observed no increase in mortality or weight loss compared to results seen with herpesvirus-negative counterparts and a relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“…We previously reported that old mice, infected with MCMV for life, and challenged with a novel pathogen (Listeria monocytogenes) in old age, mount primary CD8 T cell responses with modestly reduced effector function and bacterial clearance (12). However, in these, and other similar experiments (19)(20)(21), mortality from third-party infection was not increased by lifelong CMV infection.…”
mentioning
confidence: 74%
“…We previously reported that old mice, infected with MCMV for life, and challenged with a novel pathogen (Listeria monocytogenes) in old age, mount primary CD8 T cell responses with modestly reduced effector function and bacterial clearance (12). However, in these, and other similar experiments (19)(20)(21), mortality from third-party infection was not increased by lifelong CMV infection.…”
mentioning
confidence: 74%
“…It is important to emphasize that phenotyping for immune aging will necessarily require concurrent measurements of absolute lymphocyte counts per milliliter of blood. Namely, lowered percentages, but not absolute counts of naïve cells may also be observed due to expansions of TTDE population in persistent herpes viral infections , but this does not impair immune protection against infections . In conclusion, a combination of six markers (CD11a, CD44, CD27, KLRG1, CD62L, and CD122) allows the distinction between TN, TCM/TVM, TEM, and TTDE T cell populations in chronically infected mice (Table ), with a robust identification of age‐related losses of naïve cell populations and increases in terminally differentiated CD8 T cells, matching functional changes in aging humans.…”
Section: Flow Cytometric Phenotyping Of Cells Across Species and Tissuesmentioning
confidence: 88%
“…Latent infection with the γ-herpesvirus used in our studies, MHV68, alters the number and phenotype of memory CD8+ T cells (Barton et al, 2014). Latent MCMV infection also results in profound alteration in the T cell compartment, leading to impaired naïve T cell function (Cicin-Sain et al, 2012), despite no increase in susceptibility to secondary challenge with influenza virus, West Nile virus, or vesicular stomatitis (Marandu et al, 2015). Any or all of these mechanisms could be important contributors to co-infection associated changes in gene expression and altered antibody responses to YFV vaccination.…”
Section: Discussionmentioning
confidence: 99%